Cities in Asia by and for the People - Cabannes, Yves; Douglass, Mike; Padawangi, Rita (Amsterdam University Press, 2018)
This book examines the active role of urban citizens in constructing alternative urban spaces as tangible resistance towards capitalist production of urban spaces that continue to encroach various neighborhoods. The collection of narratives presented here brings together research from ten different Asian cities and re-theorises the city from the perspective of ordinary people facing moments of crisis, contestations, and cooperative quests to create alternative spaces to those being produced under prevailing urban processes. The chapters accent the exercise of human agency through daily practices in the production of urban space and the intention is not one of creating a romantic or utopian vision of what a city "by and for the people" ought to be. Rather, it is to place people in the centre as mediators of city-making with discontents about current conditions and desires for a better life.